Technology Shocks, Technological Collaboration, and Innovation Outcomes - Schilling, Melissa A. (Organization Science, 2015)
In the early to mid-1990s, technology alliances suddenly surged to unprecedented levels—roughly 300% growth per year from 1990 to 1995—and then declined just as precipitously. This massive increase in alliance activity caused the crystallization of a giant component in the global technology network that connected a large portion of the world’s firms, government labs, universities, and other organizations. However, when alliance activity declined, the component disintegrated. What caused this spike in alliance activity? And did this large-but-transient change in collaboration activity leave any enduring effect? The data here suggest that a major technology shock may have provoked this alliance surge. A technology shock may simultaneously unleash significant innovation opportunities while creating great uncertainty in the economic environment. Though it is well known that firms often use alliances both to respond to uncertainty and facilitate innovation, little is known about how technology shocks affect the collaboration behavior of firms and how these two factors separately influence innovation outcomes. I integrate an inductive study of collaboration activity and a technology shock with existing research on economics, alliances, and networks to build a set of arguments about how technology shocks will influence alliance behavior, how changes in alliance behavior will influence the global technology collaboration network, and about how each of these changes is likely to influence the innovative outcomes of firms. I then explore the separate and joint effects of the technology shock and collaboration activity on innovation using a large sample panel study of patenting by North American firms.